Resveratrol in Rodent Models of Parkinson’s Disease: A Systematic Review of Experimental Studies - Su, Cheng-Fu; Jiang, Li; Zhang, Xiao-Wen; Iyaswamy, Ashok; Li, Min (Frontiers in Pharmacology, 2021)
Parkinson disease (PD) is a common neurodegenerative disease featured by progressive degeneration of nigrostriatal dopaminergic neurons (DA) accompanied with motor function impairment. Accumulating evidence have demonstrated that natural compounds from herbs have potent anti-PD efficacy in PD models. Among those compounds, Resveratrol, a polyphenol found in many common plants and fruits is more effective against PD. Resveratrol has displayed a potent neuroprotective efficacy in several PD animal models. However, there is still no systematic analysis of the quality of methodological design of these studies, nor of their results. In this review, we retrieved and analyzed 18 studies describing the therapeutic effect of resveratrol on PD animal models. There are five main kinds of PD rodent models involved in the 18 articles, including chemical-induced (MPTP, rotenone, 6-OHDA, paraquat- and maneb) and transgenic PD models. The neuroprotective mechanisms of resveratrol were mainly concentrated on the anti-oxidation, anti-inflammation, ameliorating mitochondrial dysfunction and motor function. We discussed the disadvantages of different PD animal models and we used meta-analysis approach to evaluate the results of the selected studies and used SYRCLE’s risk of bias tool to evaluate the methodological quality. Our analytical approach minimized the bias of different studies. We have also summarized the pharmacological mechanisms of resveratrol on PD models as reported by the researchers. The results of this study support the notion that resveratrol has significant neuroprotective effects on different PD models quantified using qualitative and quantitative methods. The collective information in our review can guide researchers to further plan their future experiments without any hassle regarding preclinical and clinical studies. In addition, this collective assessment of animal studies can provide a qualitative analysis of different PD animal models, either to guide further testing of these models, or to avoid unnecessary duplication in their future research.